CREATIVE PROBLEM SOLVING IN LOCATION BASED SERVICES - Sehgal, Anuja; Saxena, Neelam (International Journal of Psychosocial Rehabilitation, 2020)
This paper aspires to throw light on visionary, intrapreneurship orientation among intrapreneurs who bring about unconventional, inventive changes through location based service applications. Intrapreneurship is described as an experiential, constructive process of creative problem solving, innovation initiatives within organisations to address challenging problems existing in the society.The authors primarily executed a factual, interview based fundamental research on 50 engineer’s intrapreneurial direction and creative, problem solving approach in a semi-conductor company. Intrapreneurs in a semi-conductor company have interesting idea imaginations, visualisations, formulations, innovations and thus conceive design solutions and business models that are innovative and insightful.The authors have provided crucial insights into the gradual advances in creative problem solving scenarios dealt by intrapreneurs and their notable, intrapreneurship orientation through exceptional, location-based innovative solution initiatives. The eventual results of this investigative study present efficient insights into the flourishing creative, problem resolving ways that encourage intrapreneurship orientation trends in the IT Industry. Further, it reveals, innovative work behaviour tendencies within similar technology organisations and explores the various revolutionary initiatives and their successful implementation for the social transformation of the society.The paper studies successful case stories of location based service applications and identifies successful creative problem solving approaches and intrapreneurship orientation skills for innovative value creation.